2017
DOI: 10.18632/oncotarget.22702
|View full text |Cite
|
Sign up to set email alerts
|

Association between rs3087243 and rs231775 polymorphism within the cytotoxic T-lymphocyte antigen 4 gene and Graves' disease: a case/control study combined with meta-analyses

Abstract: We conducted a case/control study to assess the impact of SNP rs3087243 and rs231775 within the CTLA4 gene, on the susceptibility to Graves' disease (GD) in a Chinese Han dataset (271 cases and 298 controls). The frequency of G allele for rs3087243 and rs231775 was observed to be significantly higher in subjects with GD than in control subjects (p = 0.005 and p = 0.000, respectively). After logistic regression analysis, a significant association was detected between SNP rs3087243 and GD in the additive and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…The study revealed that G allele in rs231775 contributes to an increased incidence in HT and GD ( 15 ). Similarly in the study of Tu et al in Chinese population G allele of rs231775 was revealed to be significantly more often in subjects with GD than in control subjects ( 66 ). Ting et al found in their work that CTLA4 SNPs A49G was associated with GD not only in Chinese adults but also and children ( 67 ).…”
Section: Discussionmentioning
confidence: 54%
“…The study revealed that G allele in rs231775 contributes to an increased incidence in HT and GD ( 15 ). Similarly in the study of Tu et al in Chinese population G allele of rs231775 was revealed to be significantly more often in subjects with GD than in control subjects ( 66 ). Ting et al found in their work that CTLA4 SNPs A49G was associated with GD not only in Chinese adults but also and children ( 67 ).…”
Section: Discussionmentioning
confidence: 54%
“…This SNP was shown to play an important role in T and B cell receptor signaling (5). The SNP rs3087243 in CTLA4 is associated with several autoimmune diseases, including SLE, RA, T1D, and Graves' disease (8,(10)(11)(12)(13)(14). The CTLA4 SNP has a protective effect, and the major allele G is associated with autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we have found a new association of TRAb titers elevated above the median and rs231775 in CTLA-4 . The variant is located in exon 1 + 49 and it was shown that the A to G substitution at this location is linked with GD [ 20 ]. A study by Ban et al found that the genotype GG in the CTLA4 A/G 49 SNP resulted in a reduced increase in T-cell proliferation compared with the AA genotype [ 21 ].…”
Section: Discussionmentioning
confidence: 99%